Spatiotemporal regulation of Aurora B recruitment ensures release of cohesion during C. elegans oocyte meiosis - Nuria Ferrandiz (Nature Portfolio, 2018)
During meiosis, step-wise release of sister chromatid cohesion mediated by REC-8 cohesin is required for the formation of haploid gametes. Here, the authors show that in C. elegans oocytes, regulated recruitment of Aurora B kinase ensures the correct distribution of REC-8 phosphorylation, which promotes cohesion release.